2019
DOI: 10.1016/j.tig.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA Splicing and Disease: Animal Models to Therapies

Abstract: Alternative splicing of pre-messenger RNA increases genetic diversity and recent studies estimate that most human multi-exon genes are alternatively spliced. If this process is not highly regulated and accurate, it leads to mis-splicing events which may result in proteins with altered function. A growing body of work has implicated mis-splicing events as contributing to a wide range of diseases including cancer, neurodegenerative diseases, and muscular dystrophies. Understanding the mechanisms that cause aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 158 publications
1
119
0
4
Order By: Relevance
“…In this study, we used the transcriptome data of different peripheral immune organs to reveal that alternative splicing events were significantly increased in response to PRRSV infection, especially the increase in the frequency of SE type. Previous reports have revealed that SE was always the most frequent alternative splicing event in a large number of animal studies [20,40]. It has been reported that the splicing level of host RNA will be changed when the virus invades the organism, which may be caused by the direct effect of the virus and the role of the immune response of the organism [4].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we used the transcriptome data of different peripheral immune organs to reveal that alternative splicing events were significantly increased in response to PRRSV infection, especially the increase in the frequency of SE type. Previous reports have revealed that SE was always the most frequent alternative splicing event in a large number of animal studies [20,40]. It has been reported that the splicing level of host RNA will be changed when the virus invades the organism, which may be caused by the direct effect of the virus and the role of the immune response of the organism [4].…”
Section: Discussionmentioning
confidence: 97%
“…Cell-specific alternative splicing is essential for normal cell function, and ~30% of all disease-causing mutations are related to RNA splicing (Montes et al, 2019). Our studies reveal the cell-specific mechanisms that govern alternative splicing of a critical synaptic calcium ion channel gene and they shed light on chronic pathology that follows nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing (AS) of pre-mRNA is the differential processing of introns and exons to generate multiple transcript isoforms from individual genes, thereby increasing molecular diversity. However, when it is not properly executed, AS leads to mis-splicing, which may result in proteins with altered function and stability 1 . A number of splicing factors and other RNAbinding proteins (RBPs) are responsible for proper regulation of AS 2 , and growing evidence has implicated mis-splicing in a range of pathologies such as cancer 3 , muscular dystrophies 4 , autism 5,6 and neurodegenerative diseases 7 such as Alzheimer´s disease 8,9 , amyotrophic lateral sclerosis 10,11 and Huntington's disease [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%